REPRESENTASI ISLAM DALAM SINETRON TUKANG BUBUR NAIK HAJI THE SERIES - Rido Budiman (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2013)
Tukang Bubur Naik Haji The Series is one of the most popular televi-sion drama in Indonesia. The series is about a poor pious muslim porridge sel-ler who could perform the expensive hajj pilgrimage. Islamic teachings domi-nate this tv drama through its plot, characters and setting. The aim of this research is to know what kind of Islamic teachings represented in the tv drama and how does the audience response about this representation of Islam in Tu-kang Bubur Naik Haji The Series. The method of the research is qualitative with the approach in Cultural Studies by using representation and encoding-decoding theory by Stuart Hall. The results are Islamic representation in this tv drama are represented through the five pillars of Islam conveyed in plot, cha-racters, and setting. The audience responded this representation of Islam through three different positions which are dominant-hegemonic, negotiated, and opposition.